Damages due to the eastern Marmara Earthquake (EME) at port structures - Yüksel, Y; Çevik, E; Çelikoglu, Y; Bostan, T; Özmen, HI; Özgüven, O (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 2001)
Izmit Bay is located at the eastern part of Marmara Sea. It is approximately 50 km length. On the 17th of August (EME), an earthquake of 7.4 magnitudes with the epicenter at the southeastern corner of the Izmit Bay caused heavy damages to the port structures. This paper summarizes type of damages recorded at different type of infrastructures such as wharfs. Especially, Derince Port is given as an example in this paper. The port includes 500m of block type quay wall at 5m to 10m water depths, 900m long piled and sheet piled quays. The port area (80.000 m(2)) behind the quay structures generally composed of fill, experienced a settlement of 70 cm due to liquefaction. Derince Port receives about 600 ships/year loading about two million tons/year of general cargoes. Containers are handled by general-purpose shore crane of 35 tons capacity. One of the wharfs is used for Ro-Ro operations. Another example Is a fishery port. The breakwater that is 230m length also suffered due to settlement in the port. However, the second earthquake is experienced in Marmara Sea near Istanbul. There is an important port, which is called Haydarpasa. Hence a scenario will be given in this paper for Haydarpasa Port, if the next segment to rupture to the west of Izmit near Istanbul because Marmara Sea stress increased up to 5 bars.
Keywords: earthquake; port; gravity quay wall; NORTH ANATOLIAN FAULT; SEA REGION; Engineering; Metallurgy & Metallurgical Engineering; Materials Science